Aplicação de modelos de insolvência nas principais empresas de call center no Brasil - Magalhães, Alex Moura (2013)
This study is the result of a financial evaluation using insolvency models applied in the financial statements of the leading call center companies operating in Brazil. These companies have great representation for the financial sector as well as great potential employment. The goal to be achieved with this study is to identify if there is risk of insolvency in these call center companies, since a research by a consultancy that accompanies the call center market raised the financial risk that occurs in the continuity of business enterprises small and medium-sized due to the high cost of investment to maintain their respective operations and not pass this cost in the final price of the service to the contractors, who do not recognize such investment as value added service